1397 'I don't have time': strategies for increasing research engagement in emergency department clinicians. Issue 12 (22nd November 2022) - Jarman, Heather; Halter, Mary; Moss, Phil; Seel, Claire
Abstract : Aims, Objectives and Background: Clinicians who engage in generating research knowledge are more likely to implement findings in practice leading to better patient outcomes. Having an emergency department (ED) culture that gives significance to research is an important factor in supporting clinicians to develop the skill and ability to participate and perform research. In 2018 the ED at St George's Hospital, London introduced an embedded research group with a dedicated leadership position, bringing together research delivery staff and clinical academics to increase the research culture in the department. This study aimed to investigate the impact of this model on research engagement amongst the ED clinical multi-disciplinary team. Method and Design: A case study design approach was used involving: A registry of the research-related initiatives undertaken in the department Analysing the metrics of engagement in research activities by clinical staff, including number of publications and academic training uptake Data were collected between April 2018 and March 2022. Results and Conclusion: Registry data show 41 distinct initiatives established in the time period led or delivered by the research group. These included face-to-face teaching, publication writing support, a research internship program and small grant funding. Research outputs (publications or conference abstracts) showed a 23-fold increase from two in 2018 to 47 in 2021. The project to develop a research culture in ED has had a positive effect on both type and number of research-related activities across all clinical staff groups. This case study illustrates how research activities delivered close to clinical practice under visible, focused clinical research leadership can increase research engagement. Challenges of a clinically complex context were overcome by embedding a multidisciplinary clinical research unit, linking research delivery with clinical academic development. This model could be replicated in other settings.